2013
DOI: 10.1111/1751-7915.12029
|View full text |Cite
|
Sign up to set email alerts
|

Trends in bacterial trehalose metabolism and significant nodes of metabolic pathway in the direction of trehalose accumulation

Abstract: SummaryThe current knowledge of trehalose biosynthesis under stress conditions is incomplete and needs further research. Since trehalose finds industrial and pharmaceutical applications, enhanced accumulation of trehalose in bacteria seems advantageous for commercial production. Moreover, physiological role of trehalose is a key to generate stress resistant bacteria by metabolic engineering. Although trehalose biosynthesis requires few metabolites and enzyme reactions, it appears to have a more complex metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 70 publications
2
98
0
2
Order By: Relevance
“…In E. coli, trehalose synthesis is catalysed by two enzymes: trehalose-6-phosphate synthase, encoded by otsA, and trehalose-6-phosphate phosphatase, encoded by otsB (Ruhal et al, 2013). E. coli produces trehalose in response to the cold (Kandror et al, 2002) and osmotic stresses (Giaever et al, 1988), during the entry into stationary phase (Hengge-Aronis et al, 1991) and in response to desiccation (Zhang & Yan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, trehalose synthesis is catalysed by two enzymes: trehalose-6-phosphate synthase, encoded by otsA, and trehalose-6-phosphate phosphatase, encoded by otsB (Ruhal et al, 2013). E. coli produces trehalose in response to the cold (Kandror et al, 2002) and osmotic stresses (Giaever et al, 1988), during the entry into stationary phase (Hengge-Aronis et al, 1991) and in response to desiccation (Zhang & Yan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To counteract these effects, bacteria protect themselves by accumulating inorganic ions (K + ) and osmoprotective organic compounds (e.g., glycine-betaine, proline, glutamate, sorbitol, mannitol, trehalose, ectoines), either by de novo biosynthesis or after uptake from the surrounding environment (Miller and Wo o d 1 9 9 6 ; C s o n k a 1 9 8 9 ) . Tr e h a l o s e ( α -Dglucopyranosyl-(1 → 1)-α-D-glucopyranoside) is a nonreducing disaccharide found in a wide variety of organisms such as bacteria, yeast, fungi, plants and invertebrates, where it can play diverse important biological roles (Lunn et al 2014;Ruhal et al 2013;Klähn and Hagemann 2011;Iturriaga et al 2009). Bacteria can use trehalose as a carbon source but also as a compatible solute, accumulated to protect cells from desiccation and osmotic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, two pathways (OtsA/B and TreS) were detected in strain YYL on the basis of whole-genome scanning (data not shown). The level of otsA transcription was higher (P Ͻ 0.01) at 84 h than that at 48 h; however, the level of transcription of the treS gene showed a slight difference between 84 and 48 h. Trehalose biosynthesis in bacteria depends on bacterial physiological requirements under the given environmental stresses (48). Interestingly, two patterns of trehalose synthesis are flexibly used by strain YYL during THF degradation, and these may be beneficial to the balance between sugar metabolism and glycolysis.…”
Section: Discussionmentioning
confidence: 96%
“…The transcriptional levels of 15 related genes involved in THF degradation, sugar and amino acid synthesis, the central genetic processes, and oxidative stress in strain YYL grown in CT were assessed over time (48,84, and 132 h) by RT-qPCR using paired primers (see Table S1 in the supplemental material). Our observations showed that the expression of thm, encoding THF-degrading monooxygenase, decreased with decreasing THF concentrations over time, with a significant change in the level of thm expression at 84 h compared with the level at 48 h being observed when the strain was grown in CT (P Ͻ 0.01) ( Fig.…”
Section: Metabolites Of Strain Yylmentioning
confidence: 99%